Clinical Efficacy and Safety of Aidi Injection Plus Docetaxel-Based Chemotherapy in Advanced Nonsmall Cell Lung Cancer: A Meta-Analysis of 36 Randomized Controlled Trials. (11th June 2018) - Xiao, Zheng; Wang, Chengqiong; Li, Lianhong; Tang, Xuemei; Li, Nana; Li, Jing; Chen, Ling; Gong, Qihai; Tang, Fushan; Feng, Jihong; Li, Xiaofei
Abstract : Background. Aidi injection is an important adjuvant anticancer drug commonly used in China. Can Aidi injection plus docetaxel-based chemotherapy improve clinical efficacy with good safety in NSCLC? To further reveal its clinical effectiveness, we systematically evaluated all the related studies. Method. We collected all the studies about Aidi injection plus docetaxel-based chemotherapy for NSCLC on Medline, Embase, Web of Science, CNKI, VIP, Wanfang, CBM, CENTRAL, Chi-CTR, and US-clinical trials. We evaluated their methodological bias risk according to the Cochrane evaluation handbook (5.1.0), extracted data following the predesigned data extraction form according to the PICO principle, and synthesized the data using meta-analysis. Results. We included 36 RCTs with 2837 patients, and most studies had unclear bias risk. The merged RR values and their 95% CI of meta-analysis for ORR, DCR, and QOL were as follows: 1.30 (1.19, 1.42), 1.17, (1.12, 1.22), and 1.73 (1.54, 1.95). The merged RR values for neutropenia, thrombocytopenia, anemia, gastrointestinal toxicity, hepatorenal dysfunctions, and alopecia were as follows: 0.70 (0.61, 0.79), 0.63 (0.53, 0.75), 0.60 (0.48, 0.75), 0.76 (0.65, 0.89), 0.56 (0.36, 0.88), and 0.58 (0.36, 0.93). Compared with chemotherapy alone, all differences were statistically significant. Subgroup analysis showed that, with 100 ml, 80-100 ml, and 50 ml, Aidi injection could increase the tumor response and Aidi injection plus DP, DC, and DO could increase the tumor response. Meta-analysis results had good stability. Conclusions. Aidi injection plus docetaxel-based chemotherapy, especially plus DP, DC, and DO, may significantly improve the clinical efficacy and QOL in NSCLC. It may also have low risk of hematotoxicity, gastrointestinal toxicity, and low risk of inducing hepatorenal dysfunctions. Aidi injection may have attenuation and synergistic efficacy to docetaxel chemotherapy. All these need to have new evidence to be proved .